Keadilan Allah dalam Penderitaan Ayub: Eksplorasi Kitab Ayub - Santo Yohanes; Nikodemus Nikodemus; Yohanes Endi (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
This paper attempts to explore the theological meaning of the Book of Job, particularly in the context of Job's suffering and God's justice. The author focuses this writing on understanding faith in suffering, with the aim of providing a deep interpretation of faith in suffering. The Book of Job is part of the Wisdom Books group consisting of 42 chapters, which discuss the suffering experienced by Job himself, and how he responded to the trials given to him by Satan with God's permission. This writing uses qualitative methods and a library research approach. This paper explains that the Book of Job provides a complex picture of the relationship between human suffering and God's justice. The main finding in this writing is highlighting the urgency of deep reflection on trust, tests of faith, and the meaning of life, leading to the conclusion that suffering is interpreted as an instrument of refining faith in God, then guiding believers towards His will and providence. Therefore, the conclusion of this paper is that suffering is interpreted as an instrument of priesthood of God, which then guides humans who believe in God's will and providence.